Recovery of resources from industrial wastewater employing electrochemical technologies: status, advancements and perspectives. Issue 1 (1st January 2021) - Devda, Viralkunvar; Chaudhary, Kashika; Varjani, Sunita; Pathak, Bhawana; Patel, Anil Kumar; Singhania, Reeta Rani; Taherzadeh, Mohammad J.; Ngo, Huu Hao; Wong, Jonathan W. C.; Guo, Wenshan; Chaturvedi, Preeti
ABSTRACT: In the last two decades, water use has increased at twice the rate of population growth. The freshwater resources are getting polluted by contaminants like heavy metals, pesticides, hydrocarbons, organic waste, pathogens, fertilizers, and emerging pollutants. Globally more than 80% of the wastewater is released into the environment without proper treatment. Rapid industrialization has a dramatic effect on developing countries leading to significant losses to economic and health well-being in terms of toxicological impacts on humans and the environment through air, water, and soil pollution. This article provides an overview of physical, chemical, and biological processes to remove wastewater contaminants. A physical and/or chemical technique alone appears ineffective for recovering useful resources from wastewater containing complex components. There is a requirement for more processes or processes combined with membrane and biological processes to enhance operational efficiency and quality. More processes or those that are combined with biological and membrane-based processes are required to enhance operational efficiencies and quality. This paper intends to provide an exhaustive review of electrochemical technologies including microbial electrochemical technologies. It provides comprehensive information for the recovery of metals, nutrients, sulfur, hydrogen, and heat from industrial effluents. This article aims to give detailed information into the advancements in electrochemical processes to energy use, improve restoration performance, and achieve commercialization. It also covers bottlenecks and perspectives of this research area. Graphical abstract: uf0001